Using digital outcrops to make the high Arctic more accessible through the Svalbox database. Issue 2 (3rd April 2021) - Senger, Kim; Betlem, Peter; Birchall, Thomas; Buckley, Simon J.; Coakley, Bernard; Eide, Christian H.; Flaig, Peter P.; Forien, Melanie; Galland, Olivier; Gonzaga, Luiz; Jensen, Maria; Kurz, Tobias; et al.
Abstract: The high Arctic is a remote place, where geoscientific research and teaching require expensive and logistically demanding expeditions to make use of the short field seasons. The absence of vegetation facilitates the use of modern photogrammetric techniques for the cost-effective generation of high-resolution digital outcrop models (DOMs). These georeferenced models can be used in pre-fieldwork activities to help prepare for traditional geological fieldwork, during fieldwork to record observations, and post-fieldwork to conduct quantitative geological analyses. Analyses of DOMs range in scale from mm-cm (e.g., size and spacing of dinosaur footprints), to hundreds of meters (e.g., seismic modeling of outcrops and outcrop-well-seismic correlations) and can advance research objectives. This integration is strengthened if key geoscientific data, like geological and topographical maps, subsurface profiles, borehole data, remote sensing data, geophysical data and DOMs can be integrated through a common database, such as the Svalbox database that we present in this commentary. Svalbox geographically targets the Svalbard archipelago, where fieldwork is challenging due to the harsh polar environment, risk of polar bear encounters and demanding transport to the field area. The University Centre in Svalbard nonetheless relies on utilizing the natural Svalbard environment for its field-based education, and now makes use of Svalbox to make geological fieldwork more efficient and post-fieldwork analyses more quantitative. Experience and usage of such tools in geoscientific education, particularly in the polar regions, is not well documented. Therefore, we share experiences on both developing and optimizing Svalbox, and on student and lecturer usage. Svalbox includes a web-based interface through which DOMs are shared and displayed together with relevant public-domain geoscientific data sets. Svalbox also serves as a platform to share student and teacher experiences on the entire DOM workflow, from acquisition to data distribution. For the Svalbox users questioned by the project group, DOMs were found to provide many benefits, including quantitative analyses, extended field season, appreciation of scale and data sharing that significantly outweigh present-day challenges, such as the need for expensive hardware and lack of easily accessible interpretation software, the latter being surmountable within the near-term.